Son of scandal - Wade, Dani (Wade, Dani. Savannah sisters., 2019)
"A member of Savannah's most influential family, Paxton McLemore has his life planned out. Until one dance at a masquerade ball leads to a night of passion with his assistant, Ivy Harden. Now Ivy is pregnant, and Paxton is falling hard. But the masks are coming off ... revealing Ivy's true identity and rekindling a blood feud that will rock Savannah society!"--Back cover.